Implementasi Inovasi Kebijakan Pembangunan Berkelanjutan di Kota Surakarta: Relokasi PKL di Taman Monumen Banjarsari ke Pasar Klitikan Notoharjo - Wijayanti, Lydia (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The relocation of Surakarta City street vendors from Taman Monumen Banjarsari to Pasar Klitikan Notoharjo is one of the innovative urban development policy focusing on cultural values aiming to strengthen local ingenuity as the city’s economic power. This study examines how the innovative policy was implemented successfully. The study showed that the success of the innovation was due to (1) the initiative and commitment of the mayor, (2) a shift in the mindset, creating trust in the management of street vendors, (3) bureaucratic reform followed by legislation of supporting documents, (4) continuous and integrated mechanism of implementation, and (5) budget cuts and focus to spending with high impact to welfare. The creation of the street vendor management manual should assure the sustainability of the innovative policy for the next term of governance.